Seasonal changes of mélange thickness coincide with Greenland calving dynamics - Yue Meng; Ching-Yao Lai; Riley Culberg; Michael G. Shahin; Leigh A. Stearns; Justin C. Burton; Kavinda Nissanka (Nature Communications)
Abstract Iceberg calving is a major contributor to Greenland’s ice mass loss. Ice mélange, tightly packed sea ice and icebergs, has been hypothesized to buttress the calving fronts. However, quantifying the mélange buttressing force from field observations remains a challenge. Here we show that such quantification can be achieved with a single field measurement: thickness of mélange at the glacier terminus. We develop a three-dimensional discrete element model of mélange along with a simple analytical model to quantify the mélange buttressing using mélange thickness data from ArcticDEM over 32 Greenland glacier termini. We observed a strong seasonality in mélange thickness: thin mélange (averaged thickness $$3{4}_{-15}^{+17}$$ 3 4 − 15 + 17 m) in summertime when terminus retreats, and thick mélange (averaged thickness $$11{9}_{-37}^{+31}$$ 11 9 − 37 + 31 m) in wintertime when terminus advances. The observed seasonal changes of mélange thickness strongly coincide with observed Greenland calving dynamics and the modeled buttressing effects.